The Effect of Lesion Location on Visuospatial Attentional Bias in Patients With Multiple Sclerosis - Kocsis Krisztián (NEUROPSYCHOLOGY, 2022)
Objective: Lateralization of visuospatial attention in healthy people, known as pseudoneglect, results in leftward bias during the Landmark or line bisection tasks. Cognitive dysfunctions in patients with multiple sclerosis (MS) might affect the visuospatial attentional abilities as well. In this study, we aimed to examine the association between atrophy and lesion location and the extent of lateralization of visuospatial attentional bias in patients with MS. Method: Visuospatial attentional bias was measured in 35 relapsing-remitting MS patients using the Landmark task. To evaluate the relation between spatial attentional bias and gray matter atrophy, voxel-based morphometry was performed on T1-weighted magnetic resonance (MR) images. In order to examine the effect of lesion location on visuospatial attentional bias, lesion-symptom mapping was conducted on the manually segmented lesions. Results: The variability of visuospatial attentional bias was higher in MS patients compared to healthy controls (p < .04). Lesion probability mapping showed that lesions located along the left superior longitudinal fascicle are associated with the extent of visuospatial bias (p < .05). No correlation was found between gray matter atrophy and the attentional bias of the patients. Conclusions: Our results indicate that lesions affecting the integrity of white matter pathways in the fronto-parietal attentional network might be accountable for the higher variability of spatial attentional bias in patients with MS.